The Photoprotective Effects of Almond Polyphenols and alpha-Tocopherol in a Three-Dimensional Human Skin Tissue Model. - Evans, Julie. (2017)
Abstract: Introduction: Almonds contain the nutrients alpha-tocopherol (AT) and almond polyphenols (AP), which have shown promise as photoprotectants in skin. Our study aims were: 1) assess the feasibility of nutrient studies in a 3-dimensinal (3D) human skin tissue model and 2) determine the photoprotection of AT and AP from ultraviolet-A (UVA) irradiation using this model. Methods and Materials: AT or AP was applied to medium (25 and 5 uM, respectively) or topically (1 mg/cm2 and 14 ug/cm2, respectively). Optimal dose and incubation time for each treatment were selected based on maximal nutrient absorption while maintaining healthy skin tissue parameters (morphology, proliferation and apoptosis). Skin absorption of AT was quantified in dermis and epidermis by HPLC with UV detection after proteolysis and standard lipid extraction. After nutrient incubation, tissues were UVA irradiated (35 J/cm2) and photodamage was assessed in comparison to control tissues after 96 h. Photodamage was assessed by morphological outcomes (basal layer organization, fibroblast presence, epidermal development) in hemotoxylin and eosin-stained tissue cross-sections; proliferation of basal cells by bromodeoxyuridine incorporation assay; apoptosis by TUNEL assay; differentiation by cytokeratin-10 immunohistochemistry; and protein secretion of growth factors, interleukin 1alpha; (IL-1alpha) and matrix metalloprotease (MMP)-2 by ELISA. Morphology and differentiation comparisons were qualitative while semi-quantitative comparisons were made for other outcome measures. Results: After 48 h medium incubation with AT, dermal and epidermal concentrations of AT were approximately 3 and 30 ng/mg wet weight, respectively. After 2 h incubation with topical AT, dermal and epidermal concentrations of AT were 1 and 37 ug/mg wet weight, respectively. Nutrient treatments alone did not induce changes in the percentage of apoptotic fibroblasts or morphologic parameters. Topical AP tended to increase percent proliferating basal keratinocytes. Topical AT treatment tended to stimulate hepatocyte growth factor (HGF), keratinocyte growth factor (KGF) and IL-1alpha. However, UVA irradiation tended to increase apoptotic fibroblasts and decrease proliferating basal keratinocytes, compared to control tissues. Negative morphologic changes were also observed at 96 h after irradiation, including disappearance of fibroblasts in the upper dermis, disorganized basal layer and less developed epithelium. UVA delayed keratinocyte differentiation and tended to suppress secretion of HGF and induce secretion of MMP-2. Tissues pretreated with all nutrient treatments tended to have increased proliferating basal keratinocytes and decreased apoptotic fibroblasts, compared to corresponding vehicle treated tissues after UVA irradiation. Morphological deterioration was partially prevented and delayed keratinocyte differentiation was attenuated by pretreatment of all nutrient applications to UVA-irradiated tissue. Pretreatment with medium and topical AT tended to stimulate HGF secretion, compared to corresponding vehicle controls after UVA irradiation. Pretreatment with medium AT, topical AT and topical AP modulated MMP-2, compared to corresponding vehicle controls after UVA irradiation. Conclusions: Our 3D skin tissue model is a feasible tool to assess nutrient photoprotection. AT absorption into dermal and epidermal compartments of this model was time and dose-dependent with concentrations reaching those found in vivo. All four nutrient treatments provided some degree of photoprotection from UVA as assessed by morphology, proliferation, apoptosis, differentiation and protein secretion. These data may have positive implications for the use of dietary and topical almond phytonutrients to prevent sun damage. This model allows for further investigation into the mechanisms by which nutrition may play a role in skin health.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Elizabeth Johnson.; Committee: C.-Y. Oliver Chen, Jonathan Garlick, and Xiang-Dong Wang.; Keyword: Nutrition.